The U.S. and the Holocaust [videorecording (DVD)] - Ward, Geoffrey C.; Coyote, Peter (PBS, 2022)
Ken Burns, Lynn Novick, and Sarah Botstein's three-part, six-hour documentary series examines how the American people and leaders responded to one of the greatest humanitarian disasters of the twentieth century, and how this catastrophe challenged America's identity as a nation of immigrants and the very ideals of democracy.